2012
DOI: 10.1038/nm.2612
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting influenza-specific CD4+ T cells correlate with disease protection against influenza challenge in humans

Abstract: Protective immunity against influenza virus infection is mediated by neutralizing antibodies, but the precise role of T cells in human influenza immunity is uncertain. We conducted influenza infection studies in healthy volunteers with no detectable antibodies to the challenge viruses H3N2 or H1N1. We mapped T cell responses to influenza before and during infection. We found a large increase in influenza-specific T cell responses by day 7, when virus was completely cleared from nasal samples and serum antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
887
7
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 902 publications
(973 citation statements)
references
References 36 publications
54
887
7
2
Order By: Relevance
“…The CD8/CD4 bead depletion was validated by Wilkinson et al 32 We found both CD4-and CD8-dependent T-cell responses in the early phases of infection (Fig. 2b).…”
Section: Rdrp-specific T-cell Responses Detected In Healthy Adults Busupporting
confidence: 75%
See 1 more Smart Citation
“…The CD8/CD4 bead depletion was validated by Wilkinson et al 32 We found both CD4-and CD8-dependent T-cell responses in the early phases of infection (Fig. 2b).…”
Section: Rdrp-specific T-cell Responses Detected In Healthy Adults Busupporting
confidence: 75%
“…44,45 Pre-existing influenza-specific CD4 + T cells were shown to correlate with disease protection in humans challenged with influenza infection. 32 HFMD is typically mild or even asymptomatic in adults, a large proportion of whom have come into contact with the virus and hence serve as a reservoir for EV71 transmission. 40 Among the most intriguing observations in the present study is that CD4-dependent EV71 RdRp-specific but not VP1-specific T-cell responses were predominantly found in healthy adults, together with the observation that there was no association between T-cell responses and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Most immune protection studies are carried out in animal models where challenge studies are feasible and mechanisms of protection can be identified by loss or gain of function. Human challenge studies are, however, becoming more frequent and have also demonstrated that cytokine‐producing memory CD4 T‐cells correlate with reduced symptoms following pathogen challenge 21, 22, 23…”
Section: Cytokine Production Is Key To Cd4 T‐cell Protective Immunitymentioning
confidence: 99%
“…29 Similarly, mice exposed to pre-pandemic H1N1 develop memory CD4 + T cells that protect against pH1N1 infection. 30 In clinical vaccine studies, a single dose of monovalent pH1N1 vaccine generates neutralizing antibodies, suggesting that memory CD4 + T cells are able to support naïve B cell responses to a novel HA. 3133 Importantly, it was shown that T cell epitopes common to pH1N1 and pre-pandemic HA stimulated memory CD4 + T cell responses; epitopes unique to pH1N1 HA failed to mount a significant CD4 + T cell response.…”
Section: Memory Cd4+ T Cells Contribute To Protection Against Influenzamentioning
confidence: 99%